Eulimnadia (Branchiopoda: Spinicaudata) in Western Australia: Three New Species and a Description of a Rediscovered Species. Issue 3 (1st May 2015) - Timms, Brian V.
Abstract: Australia has a far greater diversity of Eulimnadia than previously reported. Eulimnadia feriensis has been rediscovered and redescribed. It is unusual in having a spiniform ventroposterior projection on the telson and a spiny clasper. Three new species of Eulimnadia are also presented, each with atypical claspers and complex egg morphology. All four species occur mainly in southern Western Australia, a known hotspot for branchiopod diversification associated with long term climate change.